Incidence of End‐Stage Renal Disease Among Newly Diagnosed Systemic Lupus Erythematosus Patients: The Georgia Lupus Registry. Issue 3 (March 2016) - Plantinga, Laura; Lim, S. Sam; Patzer, Rachel; McClellan, William; Kramer, Michael; Klein, Mitchel; Pastan, Stephen; Gordon, Caroline; Helmick, Charles; Drenkard, Cristina
Abstract : Objective: To estimate and identify factors associated with the incidence of all‐cause end‐stage renal disease (ESRD) among newly diagnosed systemic lupus erythematosus (SLE) patients. Methods: Data from a national registry of treated ESRD were linked to data from a lupus registry of SLE patients who were newly diagnosed and living in Atlanta, Georgia, 2002–2004 (median followup 7.8 years). Cumulative incidence and incidence rates (ESRD treatment initiations per 1, 000 patient‐years) were calculated, and age‐ and race‐adjusted Poisson models were used to calculate incidence rate ratios (IRRs). Results: Among 344 newly diagnosed SLE patients, 29 initiated ESRD treatment over 2, 603.8 years of followup. Incidence rates were 13.8 (95% confidence interval [95% CI] 9.4–20.3) among black patients and 3.3 (95% CI 0.8–13.0) among white patients, per 1, 000 patient‐years; corresponding 5‐year cumulative incidence was 6.4% and 2.5% among black and white patients, respectively. Lupus nephritis documented prior to 2005, which occurred in 80% of those who progressed to ESRD, was the strongest risk factor for incident ESRD (IRR 6.7 [95% CI 2.7–16.8]; incidence rate 27.6 per 1, 000 patient‐years). Results suggested that patients who were black versus white (IRR 3.9 [95% CI 0.9–16.4]) or <18 years old (versus ≥30 years old) at diagnosis (IRR 2.1 [95% CI 0.9–5.3]) may be more likely to progress to ESRD, but incidence did not differ by sex or other characteristics. Conclusion: The incidence of all‐cause ESRD among patients with a recent diagnosis of SLE is high in Georgia. Interventions to decrease ESRD incidence among newly diagnosed SLE patients should target young and black patients, as well as patients with lupus nephritis.